ChemInform Abstract: Cobalt Precursors for High‐Throughput Discovery of Base Metal Asymmetric Alkene Hydrogenation Catalysts. Issue 19 (13th May 2014) - Friedfeld, Max R.; Shevlin, Michael; Hoyt, Jordan M.; Krska, Shane W.; Tudge, Matthew T.; Chirik, Paul J.
Abstract The rapid evaluation of libraries of chiral phosphine ligands with a set of simple cobalt precursors is reported.